Roncarelli’s Green Card: The Role of Citizenship in Randian Constitutionalism - Lewans, Matthew (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
This article investigates the distinct character of Randian constitutionalism and how it may have been inspired by American discourse on constitutional values. More specifically, the author examines how Justice Rand’s brand of constitutionalism is distinguishable from the more dominant strain of Diceyan constitutionalism that was prominent among Canadian jurists during the twentieth century. The author argues that the difference between Randian and Diceyan constitutionalism can be explained largely by the central role that “citizenship” played in Justice Rand’s understanding of the Canadian constitutional order.The author further argues that Justice Rand did not invent his conception of citizenship, but borrowed it from American constitutional jurisprudence regarding the Fourteenth Amendment to the Constitution of the United States. Accordingly, Justice Rand’s opinion in Roncarelli and other cases shows how his constitutional vision was shaped by a series of strong dissenting opinions concerning the now-defunct Privileges or Immunities Clause in the Fourteenth Amendment. By doing so, Justice Rand sought to install in Canadian public law the same fundamental principles of equality and non-discrimination that the American Congress intended to establish by adopting the Fourteenth Amendment.